Impact de l’utilisation d’un support image dans la relation communicative chez les enfants avec autisme - Sénia ALLAL (Corela)
The communication conveys a message that passes through language. This does not mean that it cannot pass through other codes. Therefore, it would be unwise to say that people who do not share with us the commonly accepted codes do not communicate. This is the case with persons with autism who are not in the same relationship to the world as we are. Their language can be developed only from meaningful elements and solidified by pictures/words that will anchor them in the social contract. We will discuss here creating a transverse space from the codes developed by these children and the reception we are trying to develop, giving rise to a linguistic creation in order to optimize communication.